Quentin Skinner: doniosłość i znaczenie. Komentarz tłumacza „Znaczenia i rozumienia w historii idei” - Biały, Filip (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The article accompanies the author’s translation of Quentin Skinner’s classic essay Meaning and Understanding in the History of Ideas. The article presents some biographical information about Quentin Skinner, one of the founders of ‘Cambridge School’ in history of political thought. It also comments on Skinner’s methodological positions, especially in his Meaning and Understanding in the History of Ideas (comparing the two versions of the essay – from 1969 and 2002), and his primary works. The article ends with a presentation of several critiques of Quentin Skinner’s work, but also with an appraisal of its meaning and significance to the political studies.